2021
DOI: 10.1021/acs.jafc.1c05134
|View full text |Cite
|
Sign up to set email alerts
|

Dendrobium officinale Polysaccharide Alleviates Intestinal Inflammation by Promoting Small Extracellular Vesicle Packaging of miR-433-3p

Abstract: Dendrobium officinale polysaccharide (DOP) attenuates inflammatory bowel disease (IBD), but its role in regulating cross-talk between intestinal epithelial cells (IEC) and macrophages against IBD is unclear. This study aimed to investigate DOP protective effects on the intestinal inflammatory response through regulation by miRNA in small extracellular vesicles (sEVs). Our results show that DOP interfered with the secretion of small extracellular vesicles (DIEs) by IEC, which reduced the levels of inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…On the other hand, the polysaccharides could ameliorate inflammatory bowel disease by increasing miR-433-3p in the intestinal small extracellular vesicle. The increased delivery of miR-433-3p reduced the inflammation from excessive macrophage activity in the intestine by inhibiting the MAPK signaling pathway, which was beneficial for maintaining the intestinal microenvironment [78]. Besides, the O-acetyl-glucomannan extracted from Dendrobium officinale was found to improve the colonic microenvironment and benefit colon health in mice, which increased the content of SCFAs, colonic length, and fecal moisture and reduced the colonic pH and defecation time [79].…”
Section: Gastrointestinal Modulationmentioning
confidence: 99%
“…On the other hand, the polysaccharides could ameliorate inflammatory bowel disease by increasing miR-433-3p in the intestinal small extracellular vesicle. The increased delivery of miR-433-3p reduced the inflammation from excessive macrophage activity in the intestine by inhibiting the MAPK signaling pathway, which was beneficial for maintaining the intestinal microenvironment [78]. Besides, the O-acetyl-glucomannan extracted from Dendrobium officinale was found to improve the colonic microenvironment and benefit colon health in mice, which increased the content of SCFAs, colonic length, and fecal moisture and reduced the colonic pH and defecation time [79].…”
Section: Gastrointestinal Modulationmentioning
confidence: 99%
“…Antibiotics [ 268 , 269 , 270 ] and probiotics [ 271 , 272 , 273 , 274 , 275 , 276 ] can also reduce gut inflammation through various epigenetic mechanisms. Finally, a range of Chinese herbs have been shown to have an epigenetically mediated anti-inflammatory action in the gut [ 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Paeonol from the radix of Cortex Moutan was proved to improve the inflammatory response of endothelial cells by mediating the miRNA-223 packaging in the monocytes-derived EVs [ 12 ]. Liu et al reported that the polysaccharide of Dendrobium officinale could attenuate the inflammatory bowel disease by mediating intestinal EVs with miRNA-433-5p delivering [ 31 ]. Consequently, two different EVs from VSMCs with or without peptide LSW incubation were prepared ( Figure 2 ), and the appropriate concentration of LSW was selected not to cause adverse effects on VSMCs and HVUECs ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%